Enhancing Patient-Centered Care Through Interdepartmental Synergy: A Review of Collaborative Practices in Medical Clinics - Alharbi, Turki muteb; Almutairi, Ahmed Murayshid; Almutairi, Sami Saud; Almutairi, Naif Habeeb; Almutairi, Abdulaziz Fahid; Aldowimar, Malek Abdullah; Almutairi, Eid Safer; ALHilali, Ayman Mohammed (Journal of Posthumanism, 2024)
Interdepartmental synergy within medical clinics plays a critical role in ensuring efficient and patient-centered healthcare delivery. As patients navigate multiple procedures, fragmented departmental functions often create delays, redundancies, and dissatisfaction. Collaborative practices between departments such as radiology, laboratory, pharmacy, nursing, and administration help streamline workflows, enhance communication, and reduce the risk of medical errors. This review synthesizes existing literature on interdepartmental collaboration in medical clinics, highlighting its significance in facilitating patient procedures and improving overall clinical outcomes. The findings demonstrate that integrated practices not only reduce waiting times and optimize resource utilization but also contribute to higher levels of patient satisfaction and trust. Despite the proven benefits, challenges such as departmental silos, limited digital integration, and resistance to organizational change continue to hinder effective collaboration. Addressing these barriers requires adopting patient-centered models, investing in technology-enabled solutions, and fostering a culture of teamwork. This review underscores the importance of interdepartmental synergy as a foundation for improving the quality and efficiency of healthcare services in medical clinics, and it calls for further empirical studies to develop structured frameworks for sustainable collaborative practices.